2018
DOI: 10.1016/j.envint.2017.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Environmental arsenic exposure: From genetic susceptibility to pathogenesis

Abstract: More than 200 million people in 70 countries are exposed to arsenic through drinking water. Chronic exposure to this metalloid has been associated with the onset of many diseases, including cancer. Epidemiological evidence supports its carcinogenic potential, however, detailed molecular mechanisms remain to be elucidated. Despite the global magnitude of this problem, not all individuals face the same risk. Susceptibility to the toxic effects of arsenic is influenced by alterations in genes involved in arsenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(81 citation statements)
references
References 205 publications
1
74
0
1
Order By: Relevance
“…Differential methylation and excretion rates of arsenic are also found in human populations . Hence, genetic susceptibility factors are key modulators of arsenic toxicity . Other epidemiological studies conducted in Bangladesh have reported that dietary intake of nutrients influence the toxicity of arsenic by modulating its metabolism .…”
Section: Arsenic Biotransformation and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Differential methylation and excretion rates of arsenic are also found in human populations . Hence, genetic susceptibility factors are key modulators of arsenic toxicity . Other epidemiological studies conducted in Bangladesh have reported that dietary intake of nutrients influence the toxicity of arsenic by modulating its metabolism .…”
Section: Arsenic Biotransformation and Toxicitymentioning
confidence: 99%
“…Many biochemical mechanisms have been proposed for i As as a human carcinogen . These mechanisms of action include induction of oxidative damage, activation of mitosis, and induction of genotoxic damage, interference with the methyl transfer to DNA, decrease of DNA repair mechanisms; perturbation of signaling cascades, disruption of transcriptional and translational activities, histone perturbations, differential microRNA expression, cytotoxicity and regenerative hyperplasia resulting from i AS interaction with protein sulfhydryls, and changes in genes and proteins expression . In its recent position paper, the Society of Toxicology has emphasized the need for using model systems that mimic diversity in human populations to identify biomarkers and disease endpoints at low levels of iAS exposure …”
Section: Mechanisms Involved In Arsenic Tumorigenesismentioning
confidence: 99%
“…Arsenite therefore mediates a wide spectrum of deleterious effects, bearing numerous consequences in different cells and organs, a complex scenario in apparent contrast with the simple mechanism often implicated in the effects of the metalloid. More specifically, the opinion of various groups is that a large proportion of the critical effects mediated by arsenite results from the intermediate formation of reactive oxygen species (ROS) (Flora, 2011;Minatel et al, 2018) Hence, the impact of the metalloid in different cell types should depend on their susceptibility to arsenite-induced ROS formation, in turn affected by an array of variables associated with the specific characteristics of the cells, tissues and organs. Different cells respond to arsenite by producing ROS via different mechanisms, e.g., in the mitochondrial respiratory chain (Liu et al, JPET # 262469 6 was sensitive to inhibitors of electron transport in the respiratory chain as well as to the respirationdeficient phenotype, i.e., respiration-deficient cells (RD-cells) derived from the same RP-cell line, failed to produce mitoO2 -.…”
Section: Jpet # 262469 Introductionmentioning
confidence: 99%
“…In addition to the YAP functions mentioned previously, YAP is crucial in the response to oxidative stress induced by cellular processes and by different xenobiotics as well as the development of resistance to cytotoxic agents and heavy metals (Toone & Jones, 1999). More than 200 million people in 70 countries are exposed to arsenic (As; a naturally occurring metalloid and Class A human carcinogen) through drinking water (Minatel et al, 2018). It has been reported that As induces the Hippo signaling pathway and contributes to aberrant activation, which in turn could contribute to the pathogenesis of epithelial neoplasm (Li, Srivastava, Elmets, Afaq, & Athar, 2013).…”
Section: Introductionmentioning
confidence: 99%